Refining the interpretation of variants of uncertain significance in hereditary cancer screening through integrated RNA sequencing - Youbao Sha; J. Bryce Ortiz; Sara L. Bristow; Kate Loranger; Linyan Meng; Xiaonan Zhao; Fan Xia; Sheetal Parmar; Adam C. ElNaggar; Wenbo Xu (Genetics in Medicine Open)
Purpose: Although up to 25% of germline variants are predicted to affect splicing, most are classified as variants of uncertain significance (VUS) because of the limited understanding of their functional consequences. Here, we investigated the impact of RNA sequencing (RNA-seq) data on the ability to resolve splicing-related VUS. Methods: Patients with VUS predicted to alter splicing identified through commercial hereditary cancer testing between October 2021 to July 2023 were included. RNA-seq was used to compare splicing patterns between patient blood samples and normal controls. VUS reclassification rates were calculated. Results: In total, 411 VUS in 52 genes predicted to affect splicing were included. RNA-seq results resolved 26.3% (108/411) of the VUS: 28 (6.8%) upgraded to pathogenic/likely pathogenic, and 80 (19.5%) downgraded to not reportable. Among the 28 upgraded, 17 (60.7%) were intronic, 9 (32.1%) were exonic missense variants, and 2 (7.1%) were exonic synonymous variants. Most of the VUS downgraded to not reportable were intronic (64/80, 80%). The remaining 16 (20%) of the downgraded VUS were synonymous variants. Conclusion: This study underscores the utility of RNA-seq to detect variants that affect splicing and could have an impact on cancer risk assessment management and treatment.